STRATEGI KOMUNIKASI PMI KABUPATEN TABANAN DALAM COMMUNITY EPIDEMIC AND PANDEMIC PREPAREDNESS PROGRAM - Andriyani, Putu Yunia; Amanda Gelgel, Ni Made Ras; Pradipta, Ade Devia (E-Jurnal Medium, 2021)
Community Epidemic and Pandemic Preparedness Program (CP3) is a program conducted by PMI Kabupaten Tabanan to preventive measure implemented through communication to lessen the case of dengue fever in Belalang village. The residents become more comprehend on dengue fever, including the definition, the transmission, symptoms, high-risk group, prevention, and the handling. This also influences the decreasing of dengue fever cases in Belalang village in 2019-2020, namely 40%. Therefore, through this study, the author would like to describe the communication strategy used by PMI Kabupaten Tabanan on CP3 in Belalang village. The author used the Lasswell communication model and descriptive- qualitative method in the present study. The result was Belalang have 24 village’s volunteers from all levels of society to be a communicator and comprehension on prevention of dengue fever which can be seen through behavior alteration dan affects to the decrease of dengue fever cases in Belalang village. Keywords: Communication strategy, Lasswell communication model, Community Epidemic and Pandemic Preparedness Program (CP3), PMI Kabupaten Tabanan, Dengue fever